2012
DOI: 10.2147/jmdh.s37517
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent boys with asthma – a pilot study on embodied gendered habits

Abstract: PurposeAsthma is a common chronic disease with gender differences in terms of severity and quality of life. This study aimed to understand the gendered practices of male asthmatic adolescents in terms of living with and managing their chronic disease. The study applied a sociological perspective to identify the gender-related practices of participants and their possible consequences for health and disease.Patients and methodsThe study used a combined ethnomethodology and grounded theory design, which was inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…They struggled with self-management balanced against a strong desire to interact socially with their friends. Such ambivalence was also shown in a study of adolescent boys with asthma, who described feeling disadvantaged because of their asthma, which contrasted with the statement that asthma was an insignificant part of their lives (153).…”
Section: Daily Life With Asthma (Studies III and Iv)mentioning
confidence: 95%
“…They struggled with self-management balanced against a strong desire to interact socially with their friends. Such ambivalence was also shown in a study of adolescent boys with asthma, who described feeling disadvantaged because of their asthma, which contrasted with the statement that asthma was an insignificant part of their lives (153).…”
Section: Daily Life With Asthma (Studies III and Iv)mentioning
confidence: 95%
“…Using Bourdieu's theory, researchers uncovered that negative bias of nurses and others contributed to the embodied knowledge of marginalization. As patients’ strengths and potentials were often unrecognized by health professionals, patients’ chances to cultivate relationships reduced, and patients’ opportunities to gain new competencies were limited (Cowdell, ; Edwards & Imrie, ; Gibson et al., ; Kelly, ; Thibodaux, ; Townsend, ; Westergren & Lilleaas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cowdell () found that people with dementia in an acute care setting experienced distress due to marginalization resulting from a negative image of people with dementia. Asthmatic male adolescents demonstrated ambivalence towards health care services because of a deeply embodied habitus of gendered practices (Westergren & Lilleaas, ). They sought to camouflage their diseases as a way to prevent society from viewing them as un‐masculine (Westergren & Lilleaas, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations